2022
DOI: 10.3389/fpls.2022.881965
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Grain Zinc and Iron Concentrations, Grain Yield and Associated Traits of Biofortified Bread Wheat Genotypes in Nepal

Abstract: Wheat (Triticum aestivum L.) is one of the major staples in Nepal providing the bulk of food calories and at least 30% of Fe and Zn intake and 20% of dietary energy and protein consumption; thus, it is essential to improve its nutritional quality. To select high-yielding genotypes with elevated grain zinc and iron concentration, the sixth, seventh, eighth, and ninth HarvestPlus Yield Trials (HPYTs) were conducted across diverse locations in Nepal for four consecutive years: 2015–16, 2016–17, 2017–18, and 2018–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
4
5
0
Order By: Relevance
“…In current study, strong association of Zn biofortification traits with grain yield depicts potential of simultaneous improvement in both traits. Simultaneous improvement in grain Zn traits and yield has also been reported by the other researchers [ 37 , 38 ]. Thapa et al [ 37 ] demonstrated that improvement in grain Zn contents does not compromise the grain yield in wheat.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In current study, strong association of Zn biofortification traits with grain yield depicts potential of simultaneous improvement in both traits. Simultaneous improvement in grain Zn traits and yield has also been reported by the other researchers [ 37 , 38 ]. Thapa et al [ 37 ] demonstrated that improvement in grain Zn contents does not compromise the grain yield in wheat.…”
Section: Discussionsupporting
confidence: 72%
“…Simultaneous improvement in grain Zn traits and yield has also been reported by the other researchers [ 37 , 38 ]. Thapa et al [ 37 ] demonstrated that improvement in grain Zn contents does not compromise the grain yield in wheat. The change in correlation values under different fertilization conditions may be attributed to differential response of the genotypes for specific traits under different fertilization conditions [ 14 , 20 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…PC and N were found to be highly correlated with a value of r = 0.99 (P < 0.01). Quality parameters Zn, Fe, PC, and N showed a positive correlation with each other with a significant P-value of 0.001 [19,[58][59][60][61].…”
Section: Correlation Analysismentioning
confidence: 95%
“…Similarly, five iron and zinc biofortified varieties of wheat (Himganga, Bheriganga, Khumal Shakti, Zinc Gahu-1, and Zinc Gahu-2) were released by the National Wheat Research Program (NWRP) and National Plant Breeding and Genetics Research Centre (NPBRC) in 2021 [ 15 , 17 ]. The iron and zinc content in the kernel of these varieties ranged between 32.3–41 and 34.5–54 mg kg −1 , respectively [ 18 ]. The Nepal Seed and Fertilizer Project initiated the introduction and evaluation of provitamin A and zinc biofortified maize varieties, and some of these are in the pipeline to release or register in the country.…”
Section: Introductionmentioning
confidence: 99%